Sedentary behaviors and their relationship with the metabolic syndrome components in quilombolas (Research, Society and Development, 2022)
Sedentary behaviors (SB) may be associated with components of the metabolic syndrome (MS) in quilombolas. The aim of this study is to investigate the association between SB, sitting time and TV time, with the components of MS. This is an epidemiological, cross-sectional, population-based study with quilombolas living in the microregion of Guanambi, Brazil. Data were obtained through interviews, anthropometric measurements, blood pressure measurements and blood collection. Analyzes were performed: descriptive; One-way ANOVA; MANOVA; Principal Component Analysis (PCA); and comparison by BoxPlot. The results indicate that, among the 850 quilombolas, the following prevailed: female (61.2%); with lower income (79%); and with TV time ≥5h (69.7%). In PCA, the components of MS were not associated with SB. However, the ANOVA showed that the time spent on TV, among the elderly, was associated (p